2021
DOI: 10.1186/s12891-021-04894-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcription factors and construction of a novel miRNA regulatory network in primary osteoarthritis by integrated analysis

Abstract: Backgrounds As osteoarthritis (OA) disease-modifying therapies are not available, novel therapeutic targets need to be discovered and prioritized. Here, we aim to identify miRNA signatures in patients to fully elucidate regulatory mechanism of OA pathogenesis and advance in basic understanding of the genetic etiology of OA. Methods Six participants (3 OA and 3 controls) were recruited and serum samples were assayed through RNA sequencing (RNA-seq).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In the present study, the PPI network map of the SIN for the treatment of OA was constructed using String database and Cytoscape software, and 16 underlying core targets, including ALB, IGF1, RXRA, MMP9, PPARG, PTGS2, CTSK, NR3C1, AR, BMP2, CYP2C9, ESR1, ESR2, HSD11B1, MMP1, and TGFBR1, were acquired. Among them, ALB, IGF1, RXRA, MMPs, PPARG, PTGS2, ESRs, CTSK, TGFBR1, NR3C1, and BMP2 genes are positively involved in the OA disease, [25][26][27][28][29][30][31][32] while CYP2C9 and HSD11B1 genes take parts in the inflammatory response. 33,34 The results indicated that these 16 major genes are potential core targets responsible for SIN to treat OA, and are closely associated with inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the PPI network map of the SIN for the treatment of OA was constructed using String database and Cytoscape software, and 16 underlying core targets, including ALB, IGF1, RXRA, MMP9, PPARG, PTGS2, CTSK, NR3C1, AR, BMP2, CYP2C9, ESR1, ESR2, HSD11B1, MMP1, and TGFBR1, were acquired. Among them, ALB, IGF1, RXRA, MMPs, PPARG, PTGS2, ESRs, CTSK, TGFBR1, NR3C1, and BMP2 genes are positively involved in the OA disease, [25][26][27][28][29][30][31][32] while CYP2C9 and HSD11B1 genes take parts in the inflammatory response. 33,34 The results indicated that these 16 major genes are potential core targets responsible for SIN to treat OA, and are closely associated with inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs control the outflow of target qualities by base blending to integral locales in the 3ʹ-untranslated district (3ʹ-UTR) of target mRNAs and lead to translational suppression or the debasement of the mRNAs [ 5 ]. An enormous number of past examinations have revealed that different miRNAs are involved in controlling the etiology of musculoskeletal disorders [ 6 8 ]. Lorenzo Giordano et al [ 9 ] found that multiple miRNAs were involved in the process of tendon lesions by searching multiple databases, but the use of siRNA has a very important effect on rheumatoid arthritis, tendon regeneration, and healing [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent sequencing studies in blood identified differentially expressed microRNAs in OA versus controls and in early-stage versus late-stage radiographic knee OA. 7 10 Among these, a well-powered study revealed a signature of seven circulating microRNAs to be associated with early-stage radiographic knee OA. 8 However, sequencing remains to be applied to large-scale longitudinal cohorts to identify microRNAs that are associated with disease progression.…”
Section: Introductionmentioning
confidence: 99%